The Problem with Mickey Mouse: Perceptions of Narrative and Aesthetic Value in Children’s Animated Television Adaptation - Heaney, Elizabeth (Transcr(é)ation, 2025)
In "Classic Literature and Animation: All Adaptations are Equal, but Some are More Equal than Others" (2007), Paul Wells states that, when “pure”, animation is “clearly the most effective and transparent translator of the original text” (p. 202). However, in counter to the praise that he awards the animated adaptation, Wells adds a condition, in that the animated adaptation can be "corrupted" by the presence of Mickey Mouse or Donald Duck, placing upon the animated adaptation a dichotomy in which there is a "pure," correct way to adapt, and a "corrupted," incorrect way. This article will address the value judgments placed upon children’s television adaptations, exploring how negative attitudes towards children’s media, with specific focus on attitudes towards the Disney brand, have led many children’s microadaptations to be overlooked in academic study. In doing so, this article will attempt to re-centre this argument through a close analysis of one of the animated adaptations created as part of the Mickey Mouse Works (ABC) "The Nutcracker" (1.13). Here I shall examine the narrative and stylistic approaches used to present the adapted material within this episode, asking what they can teach us about adaptation as a storytelling technique. From this, I aim to demonstrate the values these programs possess, as sophisticated examples of adaptation that we can learn from, and disrupting common assumptions on the academic worth of children’s media.